DEVELOPMENT OF AN ANDROID-BASED SIMPLE ACCOUNTING APPLICATION AS A MEDIA FOR COMPILING FINANCIAL REPORTS FOR MICRO ENTERPRISES - Darsih, Trysanti Kisria; Ginting, ‪Donny Adiatmana; Priyatna, Ryan Dhika (INFOKUM, 2022)
Actors in their business accounting records. This research has produced a research product in the form of a simple android-based accounting application. The simple android-based accounting application that was developed can be declared suitable for use if the media is valid. It is said to be valid if it has been validated by material experts and media experts. Making this simple android-based accounting application uses research and development (R&D) methods using the ADDIE development model which consists of 5 stages, namely: 1) Analysis; 2) Design (Design); 3) Development (Development); 4) Implementation (implementation); and 5) Evaluation. From the results of observations and interviews with the head of the Abadi Mangrove Women's Farmer Group that the women's group experienced problems in the production aspect, namely the limitations of equipment, where the production process still uses simple and traditional equipment as shown in the production process. The hardest thing for the Abadi Mangrove Women Farmers Group is the mixing/kneading stage of the ingredients, which still uses human labor in the process of kneading the ingredients so that the quality and quantity of the production results are not optimal. In fact, the Abadi Mangrove Women's Farmer Group is trying to develop its business, but its capital is limited. The group leader had applied for a capital loan at a rural credit bank but was rejected because he did not have business books. Financial statements are the key to monitoring business performance. Many Micro, Small, and Medium Enterprises (MSMEs) are still not aware of the importance of making financial reports. One of the reasons MSMEs do not make financial reports is that they are seen as difficult, time-consuming, inconvenient, and unimportant. Technology-based accounting records are still very rarely found, especially in MSMEs.